Anterior Gradient-2 monoclonal antibody inhibits lung cancer growth and metastasis by upregulating p53 pathway and without exerting any toxicological effects: A preclinical study. (1st May 2019) - Negi, Hema; Merugu, Siva Bharath; Mangukiya, Hitesh Bhagavanbhai; Li, Zheqi; Zhou, Bingjie; Sehar, Qudsia; Kamle, Suchitra; Yunus, Fakhar-un-Nisa; Mashausi, Dhahiri Saidi; Wu, Zhenghua; Li, Dawei
Abstract: Increased drug resistance and acute side effects on normal organs are the major disadvantages of traditional cancer chemotherapy and radiotherapy. This has increased the focus on targeted therapeutic strategies such as monoclonal antibody-based cancer therapies. The major advantage of antibody-based therapies is the specific inhibition of cancer-related targets, with reduced off-target side effects. Anterior gradient-2 (AGR2) is a prometastatic and proangiogenic tumor marker that is overexpressed in multiple cancers. Therefore, anti-AGR2 antibodies may be potential therapeutic agents for treating different cancers. In the present study, we examined a novel anti-AGR2 monoclonal antibody mAb18A4 and found that this antibody inhibited lung cancer progression and metastasis without exerting any adverse side effects on the major organs and blood in mice. Moreover, we found that mAb18A4 activated p53 pathway and attenuated ERK1/2–MAPK pathway. Furthermore, mAb18A4-treated cancer cell lines showed attenuated proliferation and colony formation, enhanced apoptosis, increased p53 expression, and reduced phosphorylated ERK1/2 expression. Treatment with mAb18A4 significantly reduced tumor size and suppressed tumor metastasis in and increased the survival of different xenograft tumor models. In addition, mAb18A4 potently suppressed AGR2-induced angiogenesis. Results of pharmacokinetic and toxicological analyses confirmed the safety of mAb18A4 as an antitumor treatment. Highlights: AGR2 antibody treatment inhibits tumor progression and prolongs survival rate without toxic effects on major organs in animal models. It inhibits AGR2 functions by p53 and MAPK pathways. Anti-AGR2 antibody therapy prolongs survival in mice. Humanized anti-AGR2 antibody has no toxic effects on major organs, making it a safe therapeutic.